National determinants of vegetarianism - Eimear Leahy; Seán Lyons; Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2010)
In this paper we use panel data regressions to investigate the determinants of vegetarianism in various countries over time. Using national level aggregate data, we construct a panel consisting of 116 country-time observations. We find that there is a negative relationship between income and vegetarianism. In relatively poor countries, vegetarianism appears to be a necessity as opposed to a dietary choice. For the well educated however, vegetarianism is becoming a more popular lifestyle choice. Results also suggest that in relatively poor countries local production of meat increases consumption of meat. This is the first paper to examine national level determinants of vegetarianism.
Keywords: 330; Ernährungsverhalten; Pflanzenbauprodukt; Einkommen; Sozialprodukt; Lifestyle; Welt